COVID-19 Pandemic and an Urgent Need of Online Learning Approaches in Nepal and Other Developing Nations - Ansari, Mukhtar (Birat Journal of Health Sciences, 2020)
COVID-19 outbreak is pandemic worldwide with increasing total reported cases, new cases and total deaths. This devastating situation has affected every corner of human lives including academic sector globally. Although there are various measures to prevent spread of COVID-19 infection, online education could be the most suitable option concerning academic institutions to curb its spread, and developing nations including Nepal are in urgent need to implement it.